Kinematic and thermal studies of the Leo Pargil Dome: Implications for synconvergent extension in the NW Indian Himalaya. Issue 9 (24th September 2014) - Langille, J. M.; Jessup, M. J.; Cottle, J.; Ahmad, T.
Abstract Building of the Himalaya and Tibetan Plateau involved an interplay between crustal thickening and extension. The NW Indian Himalaya near the Leo Pargil dome contains approximately N trending brittle normal faults and NE trending normal‐sense shear zones (i.e., bounding Leo Pargil dome) between the South Tibetan detachment system to the south and the Karakoram fault to the north. The Leo Pargil shear zone bounds the southwest flank of the Leo Pargil dome. Estimates of deformation temperatures and mean kinematic vorticity (Wm) from the shear zone were integrated with pressure‐temperature estimates to evaluate its kinematic and thermal evolution. Oblique quartz fabrics yielded kinematic vorticity estimates indicating that the rocks within the shear zone were thinned by up to 62% during W directed shearing. Top‐down‐to‐the‐W ductile deformation is recorded at temperatures from >650°C at the deepest structural levels within the dome and from 400 to 500°C at shallower structural depths. Hanging wall rocks record much lower temperatures. Pressure‐temperature data indicate that rocks in the dome were exhumed from depths of ~36 to 22 km. In contrast to other mechanisms proposed for dome formation across the Himalaya, initiation of ductile movement on the Leo Pargil shear zone occurred at midcrustal levels in a region of localized synconvergent extension at >23 Ma. The timing and kinematic setting of deformation on the Leo Pargil shear zone suggest that exhumation could be related to a localized zone of transtension near the Karakoram fault zone.